Respuesta :
Answer:
a = [tex]\frac{f+d}{c}[/tex] - b
Step-by-step explanation:
Given
c(a + b) - d = f ( add d to both sides )
c(a + b) = f + d ( divide both sides by the multiplier c )
a + b = [tex]\frac{f+d}{c}[/tex] ( subtract b from both sides )
a = [tex]\frac{f+d}{c}[/tex] - b
Answer:
[tex]\large\boxed{a=\dfrac{f+d}{c}-b=\dfrac{f+d-bc}{c}}[/tex]
Step-by-step explanation:
[tex]c(a+b)-d=f\qquad\text{add}\ d\ \text{to both sides}\\\\c(a+b)=f+d\qquad\text{divide both sides by }\ c\neq0\\\\a+b=\dfrac{f+d}{c}\qquad\text{subtract}\ b\ \text{from both sides}\\\\a=\dfrac{f+d}{c}-b\\\\a=\dfrac{f+d}{c}-\dfrac{bc}{c}\\\\a=\dfrac{f+d-bc}{c}[/tex]